Pengaruh Konseling Kelompok dengan Pendekatan Rational Emotive Behavior Therapy dalam Meningkatkan Penyesuaian Diri Santriwati - Intan Sri Ramadan; Kusnadi Kusnadi; Lena Marianti (Journal of Society Counseling, 2023)
This research is entitled "The Effect of Group Counseling with Rational Emotive Behavior Therapy Approach in Increasing Self-Adjustment Female students at the Raudhatul Ulum Islamic Boarding School, Kab. Ogan Ilir.” This research the background is that there are problems in adjusting to female students because they don't there is harmony with existing activities and procedures in the environment Islamic boarding school. This research aims first, to find out the picture group counseling with a Rational Emotive Behavior Therapy approach in improving students' self-adjustment. Second, to know the influence of group counseling with the Rational Emotive Behavior Therapy approach in improving students' self-adjustment. This research using quantitative methods with One Group Pretest and Posttest design in the experimental group, with a population of 85 female students in class VII MTs with the selected sample totaling 11 female students, the sample obtained by using purposive sampling. Data collection techniques use questionnaires and documentation. The data analysis technique uses the Wilcoxon Test with the help of the IBM SPSS Statistics Version 25 program. Research results showed that there was an increase between the pretest and experimental groups posttest with an average (mean) pretest score of 59.9091 and an average posttest score 84.9091. Group counseling with a Rational Emotive Behavior Therapy approach is in the high category, with results obtained by Asymp. Sig (2-tailed) value 0.03. Value 0.03 <0.05, it can be concluded that Ha is accepted and Ho rejected. So, from the results of this research, it can be concluded that the influence group counseling with a Rational Emotive Behavior Therapy approach influential in improving female student’s adjustment in Islamic boarding schools Raudhatul Ulum Kabupaten Ogan Ilir.